2015
DOI: 10.2337/db14-1514
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Metabolic Messages From the Gut Drives Therapeutic Innovation: The 2014 Banting Lecture

Abstract: The Banting Medal for Scientific Achievement is the highest scientific award of the American Diabetes Association (ADA). Given in memory of Sir Frederick Banting, one of the key investigators in the discovery of insulin, the Banting Medal is awarded annually for scientific excellence, recognizing significant long-term contributions to the understanding, treatment, or prevention of diabetes. Daniel J. Drucker, MD, of the Department of Medicine, Mount Sinai Hospital and the Lunenfeld-Tanenbaum Research Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 65 publications
3
67
0
Order By: Relevance
“…Thus, GIP receptor agonism augments beta cell-induced glucose-dependent insulin secretion, akin to the actions of clinically approved GLP-1 mimetics [3]. This approach is very encouraging given that the issue of GIP sensitivity in type 2 diabetes is now being addressed.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, GIP receptor agonism augments beta cell-induced glucose-dependent insulin secretion, akin to the actions of clinically approved GLP-1 mimetics [3]. This approach is very encouraging given that the issue of GIP sensitivity in type 2 diabetes is now being addressed.…”
Section: Resultsmentioning
confidence: 97%
“…The main impairments are recognised as reduced postprandial GLP-1 secretion and defective GIP receptor signalling [1]. The inadequacy in the GLP-1 arm of the incretin effect can be easily overcome through administration of exogenous GLP-1, which significantly amplifies circulating concentrations [2,3]. In contrast, pharmacological augmentation of circulating GIP levels fails to evoke an effective increase in insulin secretion in patients with type 2 diabetes [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigated whether CEACAM2 regulates insulin secretion. We report here that CEACAM2 plays a role in insulin secretion via a mechanism implicating the release of the insulinotropic glucagon-like peptide-1 (GLP-1), an incretin that potentiates glucose-stimulated insulin secretion from pancreatic ␤-cells (11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…This enhanced efficacy has been attributed to the unique type 2 diabetes phenotype in East Asians, who tend to be non‐obese and to show β‐cell dysfunction2, 5. However, differences in dietary habits might also affect the HLE of DPP4is, as the glucose‐lowering mechanisms of DPP4i involve the incretins, glucagon‐like peptide‐1 and glucose‐dependent insulinotropic polypeptide (GIP), hormones that are secreted in response to meal ingestion and enhance insulin secretion in a glucose‐dependent manner 6, 7. Indeed, we and others have shown that the HLE of DPP4i in the relatively short‐term are enhanced by fish intake, as estimated by food records and serum levels of eicosapentaenoic acids and docosahexaenoic acids, in type 2 diabetes individuals8, 9.…”
Section: Introductionmentioning
confidence: 99%